Myocardial Extracellular Volume Fraction Measured by Cardiac Magnetic Resonance Imaging Negatively Correlates With Cardiomyocyte Breadth in a Healthy Porcine Model - Zhang, Shi-Jun; Chang, Di; Jin, Ji-Yang; Wang, Ya-Ling; Wang, Lin; Wang, Yuan-Cheng; Wang, Zhen; Ju, Shenghong (Frontiers in Cardiovascular Medicine, 2022)
Background: The extracellular volume fraction (ECV) derived from cardiac magnetic resonance imaging (MRI) is extensively used to evaluate myocardial fibrosis. However, due to the limited histological verification in healthy individuals, it remains unclear whether the size of cardiomyocytes may play a potential role in the physiological changes of ECV. The aim of this study was to examine the association between cardiomyocyte size and myocardial ECV by using a healthy porcine model. Methods: Sixteen domestic healthy pigs were anesthetized and underwent cardiac MRI with mechanical controlled breathing. Intravenous contrast medium was introduced at a dose of 0.2-0.25 mmol/kg. The interventricular septum ECV was calculated using an established MRI procedure, which was based on the pre- and post-contrast T1 values of the heart and individual blood hematocrit. The cardiomyocyte breadth (CmyB) in cross section was measured by hematoxylin and eosin staining to reflect the cardiomyocyte size. Results: Data were successfully acquired from 14 pigs. The CmyB was obtained from the myocardial tissues corresponding to the region of interest on cardiac MRI. The mean ± SD of the ECV was 0.253 ± 0.043, and the mean ± SD of the CmyB was 10.02 ± 0.84 μm. The ECV exhibited a negative correlation with the CmyB (r = -0.729, p = 0.003). Conclusion: The myocardial ECV detected by cardiac MRI is negatively correlated with the CmyB in healthy pigs, demonstrating that the size of cardiomyocytes is potentially associated with the ECV under physiological conditions.